Human T cell activation induces synaptic translocation and alters expression of the serine protease inhibitor neuroserpin and its target protease. Issue 4 (10th February 2015) - Lorenz, Natalie; Loef, Evert Jan; Verdon, Daniel J.; Chen, Chun‐Jen J.; Mansell, Claudia J.; Angel, Catherine E.; Brooks, Anna E. S.; Dunbar, P. Rod; Birch, Nigel P.
Abstract : Expression and location of neuroserpin and its target tPA isregulated by T cell activation. Abstract : Contact between T cells and APCs and activation of an effective immune response trigger cellular polarization and the formation of a structured interface known as the immunological synapse. Interactions across the synapse and secretion of T cell and APC‐derived factors into the perisynaptic compartment regulate synapse formation and activation of T cells. We report that the serine protease inhibitor neuroserpin, an axonally secreted protein thought to play roles in the formation of the neuronal synapse and refinement of synaptic activity, is expressed in human nai¨ve effector memory and central memory subsets of CD4 + and CD8 + T cells, as well as monocytes, B cells, and NK cells. Neuroserpin partially colocalized with a TGN38/LFA‐1‐positive vesicle population in T cells and translocates to the immunological synapse upon activation with TCR antibodies or antigen‐pulsed APCs. Activation of T cells triggered neuroserpin secretion, a rapid, 8.4‐fold up‐regulation of the serine protease tissue plasminogen activator, the protease target for neuroserpin, and a delayed, 6.25‐fold down‐regulation of neuroserpin expression. Evidence of polarization and regulated neuroserpin expression was also seen in ex vivo analyses of human lymph nodes and blood‐derived T cells. Increased neuroserpin expression was seen in clusters of T cells in the paracortex of human lymph nodes, with some showing polarization to areas of cell:cell interaction. Our results support a role for neuroserpin and tissue plasminogen activator in activation‐controlled proteolytic cleavage of proteins in the synaptic or perisynaptic space to modulate immune cell function.